ANALYSIS OF PRODUCT QUALITY ON CONSUMER SATISFACTION WITH PROMOS I AS AN INTERVENING VARIABLE (Five mind development students) - Upik Bina Sari Maha; Manuntun Pakpahan; Mesra B (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research was conducted on students at Panca Budi Development University, Medan, on the MS Glow skincare product on the Shopee Marketplace. The aim of this research is to determine the effect of product quality on consumer satisfaction with promotion as an intervening variable. The population is active students studying at the Panca Budi Development University in Medan and samples were taken randomly using the Zikmud Formula so that the total research sample was 100 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques use literature study, survey and observation. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing. The research results show that product quality and promotion mediate the influence of product quality on consumer satisfaction with MS Glow skincare products. The strong correlation between product quality and promotion on consumer satisfaction is 43.4% and the remaining 56.6% can be explained by other variables not studied.